KESENIAN BALI DULU DAN KINI BARONG BANGKUNGâ - Anwar, Ahmad Khoirul (KEMADHA, 2012)
Culture and art is always interesting to be discussed especially in this era of globalization . Culture itself is the essence of the life of the nation . One example is the Balinese culture is predominantly Hindu teachings are rooted in the Hindu religion . Balinese culture also has a clear identity that is expressive culture which includes the basic values ??of the dominant . Bali is the appeal of the unique culture and populist. Various kinds of diversity together in creativity, taste and intention. Every religion has a feast day each, one of which is the feast day ceremonies of Hindus in Bali is Galungan . Galungan is the victory of Dharma ( goodness ) against adharma (evil ). Implementation of Galungan tinged with a series of unique and distinct in this feast enliven like Penjor in pairs in front of each house , the offerings are set high and in " sunggi " at the top of the head , and there is a uniqueness that is nearly run over by the progress of time , ie Bangkung barong . Pementasa barong bangkung are for starting reinforcements .Now this implementation barong bangkung staging seems more and more rare , especially in urban areas . Many factors influence greatly to the deterioration of this tradition, i.e is the number of incoming foreign cultures and increasing population , especially immigrants of different races and ethnicities to bring each culture to remain able to maintain this tradition into the future .